Isolation and characterization of fMGyn-Pae01, a phiKZ-like jumbo phage infecting Pseudomonas aeruginosa - Kira Ranta; Mikael Skurnik; Saija Kiljunen (Virology Journal)
Abstract Background Pseudomonas aeruginosa is an opportunistic pathogen that causes a wide variety of infections, and belongs to the group of ESKAPE pathogens that are the leading cause of healthcare-associated infections and have high level of antibiotic resistance. The treatment of infections caused by antibiotic-resistant P. aeruginosa is challenging, which makes it a common target for phage therapy. The successful utilization of phage therapy requires a collection of well characterized phages. Methods Phage fMGyn-Pae01 was isolated from a commercial phage therapy cocktail. The phage morphology was studied by transmission electron microscopy and the host range was analyzed with a liquid culture method. The phage genome was sequenced and characterized, and the genome was compared to closest phage genomes. Phage resistant bacterial mutants were isolated and whole genome sequencing and motility, phage adsorption and biofilm formation assays were performed to the mutants and host bacterium. Results The genomic analysis revealed that fMGyn-Pae01 is a lytic, phiKZ-like jumbo phage with genome size of 277.8 kb. No genes associated with lysogeny, bacterial virulence, or antibiotic resistance were identified. Phage fMGyn-Pae01 did not reduce biofilm formation of P. aeruginosa, suggesting that it may not be an optimal phage to be used in monophage therapy in conditions where biofilm formation is expected. Host range screening revealed that fMGyn-Pae01 has a wide host range among P. aeruginosa strains and its infection was not dependent on O-serotype. Whole genome sequencing of the host bacterium and phage resistant mutants revealed that the mutations had inactivated either a flagellar or rpoN gene, thereby preventing the biosynthesis of a functional flagellum. The lack of functional flagella was confirmed in motility assays. Additionally, fMGyn-Pae01 failed to adsorb on non-motile mutants indicating that the bacterial flagellum is the phage-binding receptor. Conclusion fMGyn-Pae01 is a phiKZ-like jumbo phage infecting P. aeruginosa. fMGyn-Pae01 uses the flagellum as its phage-binding receptor, supporting earlier suggestions that flagellum might be utilized by phiKZ but differs from some other previous findings showing that phiKZ-like phages use the type-IV pili as the phage-binding receptor.